A resource‐based view on the role of universities in supportive ecosystems for social entrepreneurs. (2nd September 2022) - Diaz‐Gonzalez, Abel; Dentchev, Nikolay A.
Abstract: This paper investigates the role that universities play in supporting social entrepreneurs (SEs) across their ecosystem. Adopting the resource‐based view (RBV) approach, we argue that universities attract, mobilize, and deploy multiple resources that benefit SEs through four main mechanisms (i.e., teaching, research, outreach, and the development of partnerships). We use a qualitative approach of 62 semi‐structured interviews and 8 focus groups in Ecuador, Bolivia, and Colombia. Our contribution shows that employing different resources and engaging in supportive activities of universities towards SEs facilitate the development of university capabilities, such as an increased reputation, development of leadership skills for students and staff, and wider access to ecosystem resources that support other university activities related to teaching, research, and community outreach. The role that partnerships play in the development of these capabilities is fundamental, thanks to the different strategic alliances and mobilization of resources between universities and other actors while supporting SEs. This study contributes to our understanding of the role universities can play to intensify the nature of supportive ecosystems for SEs. This contribution is relevant not only to academics but also to practitioners, as this will shed light on the building, development, and scaling of a supportive ecosystem for SEs.